La terapia conductual en el comportamiento sexual de los adultos con retraso mental leve de la fundación “Protección y Descanso” de la ciudad de Riobamba, período enero - abril 2012. - Silva Valdivieso, Diego (2012)
This research deals the influence of physical activity on sedentary children at the "Fausto Molina" School in the city of Riobamba. The children to always keep active. About physical activity and sedentary children, people discussed the importance of physical activity during childhood. Improving the availability of sceneries sports at the institutiarts workshops and other extracurricular activities were discussed as well.